2019
DOI: 10.1103/physrevd.100.115010
|View full text |Cite
|
Sign up to set email alerts
|

Correlating the anomalous results in bs decays with inert Higgs doublet dark matter and the muon g2

Abstract: In this article, we have considered an extension of the inert Higgs doublet model with SU (2)L singlet vector like fermions. Our model is capable of addressing some interesting anomalous results in b → s + − decays (like R(K ( * ) )) and in muon (g − 2). Apart from explaining these anomalies, and being consistent with other flavour data, the model satisfies relevant constraints in the dark matter sector, while remaining within the reach of ongoing direct detection experiments. The model also produces signature… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 76 publications
1
57
0
Order By: Relevance
“…[2][3][4][5]. The b → s + − anomaly is addressed by introducing a Z boson [6][7][8][9] and new particles which induce box diagram contributions [10][11][12][13][14][15][16][17][18]. Both anomalies can be explained simultaneously in models with VL fermions and a Z boson [19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5]. The b → s + − anomaly is addressed by introducing a Z boson [6][7][8][9] and new particles which induce box diagram contributions [10][11][12][13][14][15][16][17][18]. Both anomalies can be explained simultaneously in models with VL fermions and a Z boson [19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…This particular characteristic allows one to express the field modes in terms of plane wave solutions in these regions, a feature necessary for the formulation of the Hawking effect. Then with the help of the near-null coordinates [5,13,14] we provided a Hamiltonian based derivation of the Hawking effect in the Schwarzschild-Tangherlini black hole spacetime. We observed that the temperature corresponding to the Hawking effect is dependent on the spacetime dimensionality and same for both the bulk and brane-localized scalar field.…”
Section: Discussionmentioning
confidence: 99%
“…Here we define a set of near-null coordinates by slightly deforming the null coordinates [5,13,14]. In particular for observer O − we define the near-null coordinates as…”
Section: Near-null Coordinatesmentioning
confidence: 99%
See 2 more Smart Citations